The impact of takeover anticipation on rival firms. (12th December 2021) - Davis, Frederick; Davis, Svetlana; Sha, Xiaoyang; Walker, Thomas
Abstract: This paper utilizes a large, hand‐collected dataset to observe for the first time the initial wealth impact of an anticipated takeover bid on the target's rival. Distinguishing among predominant theories of acquisition probability, collusion, competitive advantage, hubris and industry growth, we find substantial evidence to support the premise that gains to rivals around the target firm's rumor date are associated with becoming either a target or a bidding firm within 1 year. Additionally, factors at the time of bid anticipation serve as useful predictors when assessing which rivals will receive or initiate a bid for corporate control. Our results demonstrate that takeover rumors represent an early and important mechanism by which information is transferred throughout an industry.